2020
DOI: 10.1108/ijssp-05-2019-0100
|View full text |Cite
|
Sign up to set email alerts
|

Active citizenship in Europe: the role of social capital

Abstract: Purpose The purpose of this paper is to show if and to what extent in the EU countries the probability of being an active citizen depends on individual/household social capital endowment, other than on individual/household socio-economic characteristics. The paper provides a deeper insight of the determinants of active citizenship due to the growing concern of the European Commission with citizens’ issues. Design/methodology/approach The core of the paper, which adopts a micro-level perspective, is an empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
0
0
1
Order By: Relevance
“…Yet, it does not clearly link civic responsibility to obedience to the law, which is seen as a mandatory responsibility [95]. Whereas the rule of law sets the principle of governance [96] and is seen as the baseline principle in Carroll's CSR [64], civic responsibility includes citizens' compliance with the rule of law [97], the act of which must be governed by justice, truth, and rationality. This view is inspired by the discussion of the case of Socrates (e.g., [58,98]), who suggested that people should not obey only those laws that they like or that may result in a good verdict for them [98].…”
Section: An Example Showing the Difficulties In Teaching Valuesmentioning
confidence: 99%
“…Yet, it does not clearly link civic responsibility to obedience to the law, which is seen as a mandatory responsibility [95]. Whereas the rule of law sets the principle of governance [96] and is seen as the baseline principle in Carroll's CSR [64], civic responsibility includes citizens' compliance with the rule of law [97], the act of which must be governed by justice, truth, and rationality. This view is inspired by the discussion of the case of Socrates (e.g., [58,98]), who suggested that people should not obey only those laws that they like or that may result in a good verdict for them [98].…”
Section: An Example Showing the Difficulties In Teaching Valuesmentioning
confidence: 99%
“…87 Aktivno građanstvo je i dalje nedovoljno razvijeno u EU, budući da se samo 12,6% građana EU može podvesti po ovaj pojam. 88 Lahuzen i Tejz (Lahusen & Theiss) ističu da su politička osvešćenost, znanje i aktivne participacije (na primer, učešće na izborima, članstvo u građanskim organizacijama i učešće u građanskim inicijativama) ključne odrednice aktivnog građanstva koje vode ka razvijanju transnacionalne solidarnosti, budući da građanima EU pružaju građanske veštine, koje su im neophodne kako bi se uključili u podršku prava drugih Evropljana. 89 Prema istraživanju Lahuzena i Tejza, građani Unije su uglavnom uključeni u inicijative i akcije solidarnosti na nacionalnom nivou, kao izvan Evropske unije, sa samo jednim od četiri ispitanika posvećenih podršci drugim građanima EU.…”
Section: Razvojni Pravci Evropske Unije Nakon Pandemije Kovid 19unclassified